PERANCANGAN SISTEM INFORMASI PROMOSI MAKANAN DI SAMULA COFFEE & EATERY UNTUK MENINGKATKAN PENJUALAN DI INDUSTRI KULINER - Prastiti, Di Ajeng; Marfin, Muhammad; Rohit, Muhammad Nur; Rievo, Louis; Nugraha, Rafif Syahril (Jurnal Ilmiah Sistem Informasi, 2024)
This research aims to design a food promotion information system at Samula Coffee & Eatery to increase sales in the culinary industry. Despite having good branding on social media, Samula Coffee & Eatery faces issues with products that are not popular and not well-known by customers. The information system developed using the linear sequential method aims to effectively introduce featured menus, promotions, and other information to customers. This system uses HTML, PHP, CSS, JavaScript, and SQL to create an interactive and user-friendly interface. The database design uses MySQL, while the website interface is designed to facilitate information access for customers. System implementation involves development, testing, user training, as well as continuous evaluation and improvement. Testing using the black-box testing method ensures that all features function according to specifications. The research results show that this information system can improve operational efficiency and product appeal at Samula Coffee & Eatery. Customers can easily access the latest information about menus and promotions and provide feedback that helps improve services. This system is expected to increase sales and customer satisfaction and serve as a reference for the development of similar information systems in other culinary industries.